Enzymatic production of fructooligosaccharides from inexpensive and abundant substrates using a membrane reactor system. Issue 9 (12th June 2016) - Ur Rehman, Amad; Kovacs, Zoltan; Quitmann, Hendrich; Ebrahimi, Mehrdad; Czermak, Peter
ABSTRACT: The concept of zero waste in the sugar industry has encouraged the development of technologies that promote utilization of by-products, including the enzymatic conversion of waste feed stocks into nutraceutical products. Here we investigated a membrane reactor for the production of fructooligosaccharides (FOS) with immobilized enzyme (Pectinex Ultra SP-L) system using pretreated molasses as substrate with cleaning efficiency and less fouling as performance tools. The resulting spectra showed a high FOS yield of 63% with 89% conversion from available sucrose. So, the enzymatic membrane reactor system with innovative continuous separation of enzyme was proved to fit for the production of FOS.